2005
DOI: 10.1534/genetics.103.015198
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Evolution of Wolbachia Compatibility Types

Abstract: Wolbachia-induced cytoplasmic incompatibility (CI) is observed when males bearing the bacterium mate with uninfected females or with females bearing a different Wolbachia variant; in such crosses, paternal chromosomes are lost at the first embryonic mitosis, most often resulting in developmental arrest. The molecular basis of CI is currently unknown, but it is useful to distinguish conceptually the male and female sides of this phenomenon: in males, Wolbachia must do something, before it is shed from maturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…The presence of several Key factors in each strain, on the other hand, is not compatible with allelic variation and must be interpreted as being (at least partly) the result of variation in gene content. Interestingly, this interpretation is compatible with current theory for the evolution of CI types (Charlat et al 2001(Charlat et al , 2005Engelstädter et al 2006) and a model of evolution in which new Lock or Key types arise by point mutations, whereas new genes are created by duplication events. In order to understand the evolution of incompatibility under this model, consider a randomly mating host population fixed for CI bacteria containing a single pair of Lock and Key loci {Lock 1 , Key 1 }.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of several Key factors in each strain, on the other hand, is not compatible with allelic variation and must be interpreted as being (at least partly) the result of variation in gene content. Interestingly, this interpretation is compatible with current theory for the evolution of CI types (Charlat et al 2001(Charlat et al , 2005Engelstädter et al 2006) and a model of evolution in which new Lock or Key types arise by point mutations, whereas new genes are created by duplication events. In order to understand the evolution of incompatibility under this model, consider a randomly mating host population fixed for CI bacteria containing a single pair of Lock and Key loci {Lock 1 , Key 1 }.…”
Section: Discussionsupporting
confidence: 87%
“…Each new CI type observed here resulted from the gain of a new resc function with no apparent change in its mod function. This supports the notion that the mod and resc functions vary independently, in agreement with the fact that these functions are encoded by different genes of the Wolbachia genome [8,11,12,15,16].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we showed that changes in CI properties of Wolbachia infecting Cx. pipiens can be observed on a laboratory time scale, and support the notion that complexity of the mod -resc system allows a more gradual transition [32,33]. Within 5 years, new CI types emerged independently in two Cx.…”
Section: Discussionsupporting
confidence: 69%
“…A likely explanation for the lack of CI induction by Wolbachia-infected males is that the Wolbachia strain has the mod À phenotype that does not modify sperm (Bourtzis et al, 1998;Merçot and Poinsot, 1998;Charlat et al, 2001;Vala et al, 2002;Zabalou et al, 2004). Males infected with mod À strains are phenotypically indistinguishable from uninfected males; they are compatible with infected as well as uninfected females.…”
Section: Discussionmentioning
confidence: 99%